Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c2lc41156c
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent digital microfluidic system with fuzzy-enhanced feedback for multi-droplet manipulation

Abstract: The complexity of droplet hydrodynamics on a digital microfluidic (DMF) system eventually weakens its potential for application in large-scale chemical/biological micro-reactors. We describe here an intelligent DMF technology to address that intricacy. A wide variety of control-engaged droplet manageability is proposed and demonstrated through the operation of our modular DMF prototype, which comprises: (i) rigid profiling ability of different droplet's hydrodynamics under a real-time trajectory track of dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…The DMFB ISA can be extended by integrating sensors [Alistar and Gaudenz 2017;Barsoukov and Macdonald 2005;Bhattacharjee and Najjaran 2012;Cooreman et al 2005;Gao et al 2013;J. Schertzer et al 2012;Lederer et al 2012;Li et al 2014Li et al , 2015Murran and Najjaran 2012;Ren et al 2004;Sadeghi et al 2012;Shih et al 2013Shih et al , 2011Suni 2008], optical detectors [Luan et al 2008[Luan et al , 2012Srinivasan et al 2004;White Royal et al 2013], heaters [Luo et al 2015], or online video monitoring capabilities [Basu 2013;Hu et al 2013;Li et al 2017;Shin and Lee 2010;Vo et al 2017].…”
Section: :3mentioning
confidence: 99%
“…The DMFB ISA can be extended by integrating sensors [Alistar and Gaudenz 2017;Barsoukov and Macdonald 2005;Bhattacharjee and Najjaran 2012;Cooreman et al 2005;Gao et al 2013;J. Schertzer et al 2012;Lederer et al 2012;Li et al 2014Li et al , 2015Murran and Najjaran 2012;Ren et al 2004;Sadeghi et al 2012;Shih et al 2013Shih et al , 2011Suni 2008], optical detectors [Luan et al 2008[Luan et al , 2012Srinivasan et al 2004;White Royal et al 2013], heaters [Luo et al 2015], or online video monitoring capabilities [Basu 2013;Hu et al 2013;Li et al 2017;Shin and Lee 2010;Vo et al 2017].…”
Section: :3mentioning
confidence: 99%
“…21 The ITO (Indium Tin Oxide) coated glasses were purchased from HuaNan Tehnology Ltd (China) to serve as the bottom plate of the DMF device. The step-by-step assembly as well as the operation of the µNMR relaxometer can be found in the ESI video 1.…”
Section: Dmf Device and Electronicmentioning
confidence: 99%
“…[20][21][22][23] DMF is also bio-compatible and has been adopted in a wide variety of applications, including cell culturing, [24][25][26] DNA amplification [27][28][29] and single protein molecule capturing. [20][21][22][23] DMF is also bio-compatible and has been adopted in a wide variety of applications, including cell culturing, [24][25][26] DNA amplification [27][28][29] and single protein molecule capturing.…”
Section: Introductionmentioning
confidence: 99%
“…Using a multiplexed ring-oscillator-based sensing circuit, Gao et al 50 showed that multi-droplet sensing could provide additional advantages (Fig. 5b).…”
Section: Droplet Transportmentioning
confidence: 99%